ASA DALAM ALUNAN GULA GENDING : STUDI TENTANG PANDANGAN MASYARAKAT DESA KEMBANG KERANG DAYA TENTANG PENDIDIKAN - Inderasari, Oryza Pneumatica; Fatoni, Haerul Rizal; Maulana, Ikmal; Sopian, Muhammad Ali (Universitas Wijaya Kusuma Surabaya, 2021)
Poverty, for some people, is not always followed by low education. This is evidenced by the experience of the gula gending sellers who can send their children to higher education. This research was completed using a qualitative descriptive method with the help of the social construction theory of Peter L. Berger and Luckman. Sources of data used are primary and secondary data. Bringing up the title